Research on the equivalent relationship of torpedo penetrated by underwater supercavitation projectile based on energy consumption model. (March 2020) - Zhao, Y L; Yan, P; Li, X; Tan, B; Wei, P
Abstract: Supercavitation projectile is one of the research hotspots of underwater defence technology. The cost of underwater damage test is such high that equivalent test on land is often considered as a possible alternative. In this paper, the equivalent relationship between torpedo and related materials penetrated by underwater supercavitation projectile is studied. Firstly, a typical torpedo structure model consisting of the torpedo shell and 14 key components is constructed; Secondly, the process of underwater supercavitation projectile penetrating torpedo is divided into two stages, that is, the underwater motion of projectile before penetration and the projectile penetrating torpedo. And the energy consumption models of projectile penetrating water medium and the energy consumption models of projectile penetrating torpedo are established respectively, considering the influence of water medium on torpedo. Because the equivalent targets obtained by the vertical impact of the projectile are different at different positions of the torpedo, two typical penetration directions and typical cabin sections of the control section of the torpedo are considered in this paper. Finaly, combined with the water medium model and torpedo structure model, and based on the principle of equivalent ultimate penetration velocity and equal minimum penetration energy consumption, the full torpedo equivalent simulation model of transverse penetration and longitudinal penetration torpedo control section under underwater penetration condition considering the influence of water medium is established.